2010
DOI: 10.1183/09031936.00024410
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery pressure limits exercise capacity at high altitude

Abstract: Altitude exposure is associated with decreased exercise capacity and increased pulmonary vascular resistance (PVR).Echocardiographic measurements of pulmonary haemodynamics and a cardiopulmonary exercise test were performed in 13 healthy subjects at sea level, in normoxia and during acute hypoxic breathing (1 h, 12% oxygen in nitrogen), and in 22 healthy subjects after acclimatisation to an altitude of 5,050 m. The measurements were obtained after randomisation, double-blinded to the intake of placebo or the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 37 publications
4
108
0
Order By: Relevance
“…Thus interefering with endothelin-1 signaling could potentially affect lung diffusing capacity by pulmonary and renal fluid retention. However, the intake of the endothelin A receptor blocker sitaxsentan did not affect the renal handing of sodium and water in healthy volunteers at 5,050 m (34). In the present study, the observed effects of sitaxsentan are thus most likely related to a specific pulmonary hemodynamic effect.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Thus interefering with endothelin-1 signaling could potentially affect lung diffusing capacity by pulmonary and renal fluid retention. However, the intake of the endothelin A receptor blocker sitaxsentan did not affect the renal handing of sodium and water in healthy volunteers at 5,050 m (34). In the present study, the observed effects of sitaxsentan are thus most likely related to a specific pulmonary hemodynamic effect.…”
Section: Discussionmentioning
confidence: 54%
“…The echocardiography and the incremental cycle ergometer CPET were performed as previously reported (34). The hemodynamic measurements relevant to the present study were cardiac output (Q) and pulmonary artery pressure (PAP), estimated, respectively, from the left ventricular outflow tract time-velocity integral and the maximal velocity of tricuspid regurgitation (TRmax).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Exercise exacerbates CaO 2 reduction due to the lower uptake of O 2 during gas exchanging in the lungs, 1,19 which may increase the risk of pulmonary edema, 11,20 especially in people predisposed to suffer this complications associated to rapid ascent. 21 Considering that the increase in PAP could be an important factor limiting performance during exercise in hypoxia, 22 sildenafil has been proposed as a potential ergogenic aid for physical activity in hypoxic conditions due to its possible benefits for athletic performance, and has been widely used. 23---27 This could be of especial interest in some countries, such as Andean or central Asia plateaus, where many professional athletes and football and other collective sport teams have to perform or play in locations higher than 2500 m. Finally, sildenafil use has also been promoted under the name of ''Vitamin V'' in some Internet forums because it supposedly improves muscle hypertrophy in bodybuilders and fitness enthusiasts.…”
Section: Hypoxia and Exercisementioning
confidence: 99%